Akses dan Kontrol Politik Perempuan Etnis Cina dalam Pemilu Legislatif 2004 di Kota Padang - Rafni, Al (Jurnal Demokrasi, 2007)
This study intended to provides an explanation about the access and control of Chinese Women inÂ  general election 2004 in Padang. The data is collected from 180 respondents in Kelurahan Pondok, Kecamatan Padang Barat, Padang CityÂ  through questionnaire and analyzed by using quantitative descriptive method. Data was also collected through deep interview and analyzed by using interactive model analysis. The finding of this research indicated that the access of Chinese women in general election tended to be low except as voters. The low access is parallel to their weakness of control in the election. Kata Kunci: Akses politik, kontrol politik, perempuan etnis Cina, pemilu legislatif